2017
DOI: 10.3892/ol.2017.6045
|View full text |Cite
|
Sign up to set email alerts
|

Anti-rheumatic drug iguratimod protects against cancer-induced bone pain and bone destruction in a rat model

Abstract: The bone is one of the most common sites of metastasis in patients with cancer. Current treatments for bone metastases include bisphosphonates, denosumab, non-steroidal anti-inflammatory drugs and analgesics, but each of them has certain limitations. Cytokines and mediators released from various cells in the bone microenvironment may drive a vicious cycle of osteolytic bone metastases. Iguratimod (T-614), a novel disease-modifying anti-rheumatic drug, has demonstrated therapeutic effects by suppressing the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Besides, some recent studies also have highlighted the potential benefits of IGU on bone metabolism in other clinical circumstances other than RA. For example, in vitro and in vivo studies have consistently showed that IGU could effectively protect against cancer-induced bone pain and bone destruction, probably via downregulating interleukin-6 production in a nuclear factor- κ B-dependent manner [ 54 , 55 ]. Moreover, an early study has also suggested a directly inhibitory role of IGU on osteoclast formation and function, which may also be a candidate mechanism underlying the preventative efficacy of IGU against bone destruction [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, some recent studies also have highlighted the potential benefits of IGU on bone metabolism in other clinical circumstances other than RA. For example, in vitro and in vivo studies have consistently showed that IGU could effectively protect against cancer-induced bone pain and bone destruction, probably via downregulating interleukin-6 production in a nuclear factor- κ B-dependent manner [ 54 , 55 ]. Moreover, an early study has also suggested a directly inhibitory role of IGU on osteoclast formation and function, which may also be a candidate mechanism underlying the preventative efficacy of IGU against bone destruction [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sun et al reported the efficacy of iguratimod in a rat model of cancer-induced bone pain as analyzed by mechanical paw withdrawal and pERK and c-Fos measurements in the spinal cord. 63 In addition, bone destruction was detected by histopathology and X-ray (Fig. 5).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the majority of studies in the literature that used the Walker 256 breast cancer cell-induced bone pain model in rats, used the hind "paw" as a location to test hypersensitivity to evoked pain such as that induced by the von Frey test, rather than spontaneous or movement evoked pain (Cheng et al, 2016, Yao et al, 2011, Sima et al, 2016, Luo et al, 2016, Shenoy et al, 2016. There are many different studies recently published in 2017 to date, that used Walker 256 cells to induce bone pain in rats that only used stimuli evoked behavioural measures such as von Frey paw withdrawal thresholds in the hindpaws, but not spontaneous movement evoked or weight bearing measures to assess pain hypersensitivities (Liu et al, 2017b, Liu et al, 2017a, Yao et al, 2017, Sun et al, 2017b, Sun et al, 2017a, Dai et al, 2017, Hou et al, 2017, Hang et al, 2017, Zhou et al, 2018. However, in the preclinical research field of cancer induced bone pain, pioneering efforts are being made to introduce novel methods to assess hypersensitivity, like application of stimulus directly to the tibia (Falk et al, 2015a) or assessment of grid climbing behaviours (Falk et al, 2017).…”
Section: Future Directionsmentioning
confidence: 99%